System zaopatrzenia w wodę w gminie Kotla = Water supply system in Kotla commune - Ogiołda, Ewa; Gniewosz, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Water supply systems are expensive ? so it is important to design and exploit them in such way they can operate and be reliable for a long time. In this paper parameters of exploited system and their changes caused by rise of water consumption were analysed.
Keywords: system zaopatrzenia w wodę; obliczenia hydrauliczne; water supply system; hydraulic calculations